Evaluation of the insect growth regulator lufenuron (MatchA (R)) for control of aedes aegypti by simulated field trials - Salokhe, S. G.; Deshpande, S. G.; Mukherjee, Samindra N. (Parasitology Research, 2012)
The insect growth regulator, Lufenuron, at concentrations of even multiples of LC90 (determined under laboratory conditions) was tested against the III instar larvae of Aedes aegypti under simulated field conditions. For all concentrations tested, 100 % mortality of the larvae was observed within 24 h of exposure to Lufenuron-treated water. In experiments with LC90 x 4 Lufenuron concentration and where 15 % of water volume was replaced daily, percent mortality of the larvae was reduced to 40 % after the 54th day of treatment. Percentage mortality of the III instar larvae on the 54th day was higher in water with LC90 x 6 concentration than that observed for water with LC90 x 4 of Lufenuron. In the experiments with LC90 x 4 and LC90 x 6 concentrations of Lufenuron where 15 % of water volume was replaced weekly, larval mortality obtained after the eighth week was 68.75 and 88.33 %, respectively. In LC90 x 4 and LC90 x 6 of Lufenuron-treated stagnant water (without replacement of water), the percent mortality of the larvae on the 55th day was 65 and 90 %, respectively. Introducing a fresh batch of III instar A. aegypti larvae in the Lufenuron-treated waters revealed that residual activity of Lufenuron was sustained for 45 days after the treatment. All these experiments revealed that Lufenuron not only affects the prevalence of the A. aegypti larvae but also induces the development of abnormal adults.